MILLENNIALS’ UNDERSTANDING OF STAYCATION CONCEPT TRENDING AFTER CRISIS - Zulkefli, Nor Syuhada; Mohd Alwi , Siti Nazatul Anis; Mansor, Nur Aliah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The staycations gained popularity as an alternative form of leisure. Staycations involve spending time in nearby locations, typically within one’s local environment, to relax and unwind. Millennials and Generation Z are particularly drawn to this trend because they prefer new experiences, convenience, and cost savings. This study used a qualitative approach using in-depth interviews to explore the key terms of the staycation concept, focusing on their behaviors, perceptions, and experiences in Malaysia. The main finding found five themes to describe of staycation concept among Millennials, which are length of stay, distance, intention, flexibility, and the desire to explore local destinations. Findings suggest that staycations are not only a practical alternative to traditional vacations but also a meaningful experience that promotes relaxation, sustainability, and connection to local culture.